Análisis técnico – económico de alternativas de reemplazo para la disposición final del cargador frontal VOLVO L120F en Summa Gold Corporation - De la Cruz Peláez, Oscar (2023)
The main objective of the research was to determine the best replacement alternative for the final disposal of the VOLVO L120F front loader by means of a technical-economic analysis at the Isabelita mining unit of Summa Gold Corporation S.A.C. The methodology used was a non-experimental, descriptive and applicative design. The population consisted of all front loaders in final disposal condition in the Isabelita-Summa Gold Corporation SAC unit and the sample consisted of the VOLVO L120F front loader in depreciated condition in the Isabelita unit. The results obtained were that it was possible to determine and compare the technical specifications between the VOLVO L120F and CAT 950L front loaders, where the CAT 950L front loader has better technical specifications than the VOLVO L120F loader, the differences obtained between both loaders are that the shovel capacity is 0.3 m3 , engine power of 300 RPM and 6 liters of fuel volume. The costs of possession and operation of the VOLVO L120F front loader in OverHaul condition were also determined, where the hourly cost of possession was 83.33 soles/hour, and the cost of operation was 184.52 soles/hour. Likewise, the cost of possession and operation of the CAT 950L front loader as a renewal alternative was determined, being the hourly cost of possession 43.69 soles/hour and the cost of operation 167.14 soles/hour. The total costs of the front loaders were compared, with a difference in total hourly cost of 57.52 soles/hour and a total difference of S/. 690,240.00. Finally it is concluded that based on the analysis and certain calculations it is determined that the VOLVO L120F front loader requires a renewal, since the total cost of the OverHaul is higher in S/. 690 240.00 than the total cost of the CAT 950L.